The prevalence of dysbetalipoproteinaemia in Ghanaian adults living in Accra - Ateko, Richmond Owusu (Department of Clinical Laboratory Sciences, 2024)
Background Dysbetalipoproteinaemia (dysβ) is a disorder characterised by elevated triglyceride-rich lipoprotein remnants leading to increased plasma levels of total cholesterol and triglyceride. Dysbetalipoproteinaemia is positively associated with premature cardiovascular disease. In several places worldwide, especially in sub-Saharan Africa, clinicians often miss the diagnosis of dysβ due to a lack of awareness of the disorder and its manifestations. Although the apo E2/2 isoform is the most common genetic cause of dysβ, other mutations in apo E, which are autosomal dominant, can also cause dysβ. The apo E arginine 145 cysteine (R145C) is such a mutation and is highly prevalent in the indigenous African population of South Africa. Its prevalence in Ghana is unknown. Aim The main aim of this study was to determine the prevalence of dysβ by a diagnostic electrophoresis technique in Ghanaians living in Accra, and to establish the genetic associations. Method(s) The study recruited 1032 participants, comprising 702 healthy controls, 268 diabetic patients, and 62 ischaemic heart disease (IHD) patients. Adult men and postmenopausal women were studied as dysβ is most commonly identified in these demographic groups. Anthropometric measurements and blood pressure readings were taken and recorded after participants consented. Blood samples were collected to analyse concentrations of creatinine, glucose, and triglyceride, total cholesterol, HDL-c, and calculated LDL-c. DNA analyses were conducted to identify the presence of the apoE genotype and the frequency of apoE (R145C) in the study population. Non-denaturing polyacrylamide gradient gel electrophoresis (PGGE) was used to screen for the dysβ phenotype by determining whether remnant-sized lipoproteins had accumulated in the characteristic pattern of dysβ Findings The study revealed the presence of dysβ within a subset of the Ghanaian population, with a notable association observed among individuals exhibiting apo ԑ2/2 homozygosity. Moreover, the study shed light on the utility of PGGE as an economical and practical screening tool for identifying dysβ cases. Additionally, investigating the clinical implications associated with dysβ in the Ghanaian population could provide valuable insights for healthcare providers and policymakers